Antagonism Test of Trichoderma atroviride and Gliocladium sp. Bali Local Isolates As a Disease Control of Blendok Disease (Botryodiplodia theobromae) in Grapefruit (Citrus grandis L. Osbeck) - Putu Krisnawan Kalimutu; Ida Bagus Komang Mahardika; Putri Risa Adriani Anak Agung Sagung (Warmadewa University Press, 2020)
This study aims to determine the ability of Trichoderma atroviride and Gliocladium sp. in inhibiting the fungus that causes Gumosis disease Botryodiplodia theobromae. This study used a completely randomized design with two single treatments and was repeated eight times. In the in-vitro antagonism test Trichoderma atroviride and Gliolcadium sp. can inhibit the fungus Botryodiplodia theobromae as well. The percentage of inhibition was 94.58% in the Trichoderma atroviride antagonism test and 81.67% in the Gliocladium sp. antagonism test. Whereas the Botryodiplodia theobromae Colony Area had no significant effect on both treatments. Each Botryodiplodia theobromae Colony area is 18.34 cm2 with T. atroviride treatments and 22.25 cm2 with Gliocladium sp. treatment. The growth rate of Botryodiplodia Theobroma fungi was superior to that of Trichoderma atroviride and Gliocladium sp.